دور قواعد الاختصاص القضائي الدولي في حماية المستهلك الإلكتروني - تدريست, كريمة (University of Eloued جامعة الوادي, 2020)
أضحت عقود المستهلكين المبرمة عبر الإنترنت من أهم وسائل انتعاش التجارة الإلكترونية العابرة للحدود، غير أنها تثير إشكاليات قانونية كثيرة تمثل تحديا للنظم القانونية القائمة، منها إشكالية تحديد الاختصاص القضائي الدولي بنظر المنازعات الناشئة عنها. ولمن المستقر عليه أن النظم القانونية المقارنة وضعت قواعد تسمح بتحديد الاختصاص القضائي الدولي في مجال العلاقات الخاصة الدولية، إلا أن مقتضيات إعمال مبدأ حماية الطرف الضعيف في هذه العلاقات أدى إلى التساؤل عن قدرة هذه القواعد على توفير الحماية للمستهلك الإلكتروني. لذلك تبحث هذه الدراسة عن فاعلية قواعد الاختصاص القضائي الدولي في توفير الحماية اللازمة للمستهلك الإلكتروني، ببيان القصور الذي يعتري القواعد التقليدية للاختصاص القضائي الدولي وإبراز الحاجة إلى تكريس قواعد اختصاص قضائي خاصة لتحقيق الهدف المنشود. Online consumer contracts have become one of the most important means for the recovery of cross-border e-commerce, but they raise many legal problems that represent a challenge to existing legal systems, including the problem of defining international jurisdiction with regard to disputes arising from them. It is established that comparative legal systems have established rules that allow the determination of international jurisdiction in the field of international private relations, but the requirements for the implementation of the principle of protection of the weak party in these relationships led to a question about the ability of these rules to provide protection to the electronic consumer. Therefore, this study searches for the effectiveness of the rules of international jurisdiction in providing the necessary protection for the electronic consumer, by showing the deficiencies in the traditional rules of international jurisdiction and highlighting the need to devote special jurisdiction rules to achieve the desired goal.
مجلد11، عدد3
Keywords: الاختصاص القضائي الدولي، المستهلك الإلكتروني، التجارة الإلكترونية، التعاقد عبر الإنترنت.; International jurisdiction, E-consumer, E-commerce, Online contracting